Plasma immersion ion implantation on 15-5PH stainless steel: Influence on fatigue strength and wear resistance - Bonora, R. [UNESP]; Cioffi, M. O.H. [UNESP]; Voorwald, H. J.C. [UNESP] (IOP Publishing, 2017)
Surface improvement in steels is of great interest for applications in industry. The aim of this investigation is to study the effect of nitrogen ion implantation on the axial fatigue strength and wear resistance of 15-5 PH stainless steel. It is well know that electroplated coatings, which are used to improve abrasive wear and corrosion properties, affects negatively the fatigue strength. It is also important to consider requirements to reduce the use of coated materials with electroplated chromium and cadmium, that produce waste, which is harmful to health and environment. The HVOF (High velocity oxygen fuel) process provides hardness, wear strength and higher fatigue resistance in comparison to electroplated chromium. Plasma immersion ion implantation has been used to enhance the hardness, wear, fatigue and corrosion properties of metals and alloys. In the present research the fatigue life increased twice for 15-5 PH three hours PIII treated in comparison to base material. From the abrasive wear tests a lower pin mass reduction was observed, associated to the superficial treatments. The improvement of fatigue and mechanical performance is attributed to a combination of nitrides phase structure and compressive residual stresses during the PIII treatment.